miR-21, Mediator, and Potential Therapeutic Target in the Cardiorenal Syndrome - Huang, Cheng-Kai; Bär, Christian; Thum, Thomas (Frontiers in Pharmacology, 2020)
Oligonucleotide-based therapies are currently gaining attention as a new treatment option for relatively rare as well as common diseases such as cardiovascular disease. With the remarkable progression of new sequencing technologies, a further step towards personalized precision medicine to target a disease at a molecular level was taken. Such therapies may employ antisense oligonucleotides to modulate the expression of both protein coding and non-coding RNAs, such as microRNAs. The cardiorenal syndrome (CRS) is a complex and severe clinical condition where heart and renal dysfunction mutually affect one another. The underlying mechanisms remain largely unknown and current treatments of CRS are mainly supportive therapies which slow down the progression of the disease, but hardly improve the condition. The small non-coding RNA, microRNA-21 (miR-21), is dysregulated in various heart and kidney diseases and has been repeatedly suggested as therapeutic target for the treatment of CRS. Impressive preclinical results have been achieved by an antisense oligonucleotide-based therapy to effectively block the pro-fibrotic traits of miR-21. Since microRNA-mediated pathways are generally very well-conserved, there is considerable commercial interest with regards to clinical translation. In this review, we will summarize the role of miR-21 within the heart–kidney axis and discuss the advantages and pitfalls of miR-21 targeting therapeutic strategies in CRS.